Preferential corrosion in ASTM A572 Gr 50 steel welds: role of input heat and acid concentration - Polo Briceño, Elmer Rolando; Zavaleta Gutierrez, Nilthon Emerson; Sandoval Ochoa, Joel Johnny; Briceño Roldan, Federico Braulio; Ñique Gutierrez, Norberto Damián (LACCEI, 2025)
This study investigates the influence of varying heat input levels and hydrochloric acid (HCl) concentrations on the microstructural alterations and corrosion behavior of ASTM A572 Grade 50 steel welded joint. An increase in heat input from 1.2 kJ/mm to 2.2 kJ/mm produces significant changes in the microstructure, which in turn directly affect the corrosion response. In detail: (a) in the weld metal (last pass), the ferrite microstructure evolves from acicular and grain boundary ferrite to polygonal ferrite combined with aligned M-A-C ferrite; (b) in the coarse-grained HAZ, a transition from fine martensite to coarse martensite is observed; (c) in the fine-grained HAZ, very fine-grained ferrite appears; and (d) in the intercritical (ICZH) and subcritical (SCZH) zones, spheroidized pearlite structures develop. As the concentration of hydrochloric acid (HCl) in the medium increases, the corrosion rate in different regions of the welded joint also increases. Electrochemical experiments—including open-circuit potential (OCP), potentiodynamic techniques, and linear polarization resistance—provide evidence that the weld metal exhibits cathodic behavior in the galvanic couples formed within the joint. In contrast, the heat-affected zone and the base metal exhibit anodic behavior. Regarding the corrosion mechanism, potentiodynamic tests indicate that the process is governed by activation control.